Ratnakūṭa Studies, Volume I - Felbur, Rafal, (Asian Studies E-Books Online, Collection 2025., 2025)
Indian Mahāyāna Buddhist traditions produced hundreds of scriptures and treatises, only a small number of which have received serious scholarly attention. The present volume inaugurates the Buddhist Open Philology Project (BOPP) publication series, which aims to produce state-of-the-art critical editions, translations, and studies of individual works, thereby seeking to advance the comprehensive study of Buddhism's vast literary tradition. This volume collects four studies on the composition and impact of the collection of scriptures called the Mahāratnakūṭa ("Great Heap of Jewels"), including critical editions and translations of two scriptures. Contributors are: Jonathan A. Silk, †Gadjin M. Nagao, and Michael Radich.